Bilateral simultaneous breast reconstruction with transverse musculocutaneous gracilis flaps. Issue 1 (January 2015) - Bodin, Frédéric; Schohn, Thomas; Dissaux, Caroline; Baratte, Alexandre; Fiquet, Caroline; Bruant-Rodier, Catherine
Summary Background A transverse musculocutaneous gracilis flap provides good autologous reconstruction for small- and medium-sized breasts. Although the procedure is well adapted for bilateral breast reconstruction, no publication has specifically addressed simultaneous bilateral cases. Methods From 2010 to 2014, the authors performed seven simultaneous bilateral breast reconstructions using transverse musculocutaneous gracilis flaps. The results with respect to operative data, immediate complications, second-stage reconstruction, and patient satisfaction after >1 year of follow-up were studied retrospectively. Results The mean operative time was 7 h and 48 min (range, 6–9 h). Three minor complications occurred: two cases of limited flap necrosis and one case of donor-site wound dehiscence. Surgical revision was not required, and there was no flap failure. A second-stage operation was performed in 71% of the patients to improve the aesthetic results and flap volume. On average, 167 cm3 of fat was injected per breast. After a mean follow-up of 27 months, the satisfaction rate was 86% without significant functional deficits. Conclusions A transverse musculocutaneous gracilis flap is an effective and safe option for simultaneous bilateral reconstruction. The operating time is shorter than that for other autologous procedures with similar complication rates and high patient satisfaction levels.